1992
DOI: 10.2166/wst.1992.0173
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Origins, Deposition and Build-Up in Combined Sewer Systems

Abstract: The origins of sediments and associated pollutants found in sewers are clear, and demonstrable temporal and spatial variations have been found. It is likely that these variations are such that it is not possible to formulate general rules for the rates and nature of surface wash-in to sewers. Sanitary sources, however, are more amenable to deterministic assessment. The rates of build-up of sediments in sewers vary widely, and whilst it is possible to estimate the build-up in small-sized collector sewers, no ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…Table 3, the sediment increase rates vary widely, because of the wide range of the various types of solids, the service area and the highly variable nature of in-sewer flow regimes, which are consistent with previous research (Ashley and Crabtree, 1992;Pisano et al, 1998). On the other hand, the results in Table 3 suggested that the sediment accumulation rate is high at first and then decreases gradually.…”
Section: Dynamic Tendency Of the Sediment Layersupporting
confidence: 89%
“…Table 3, the sediment increase rates vary widely, because of the wide range of the various types of solids, the service area and the highly variable nature of in-sewer flow regimes, which are consistent with previous research (Ashley and Crabtree, 1992;Pisano et al, 1998). On the other hand, the results in Table 3 suggested that the sediment accumulation rate is high at first and then decreases gradually.…”
Section: Dynamic Tendency Of the Sediment Layersupporting
confidence: 89%
“…(15)) [12]. The sewer sediment load model of the Cleveland City considered only the tube length, average slope and per capita flow, but the sewer sediment load model of the Fitchburg City and the Boston City considered average diameter of pipes, sewer service area, average slope of pipelines and total length of drain.…”
Section: Sediment Load Models and Pollution Load Models Of Combimentioning
confidence: 99%
“…Le modèle Horus comporte cinq modules principaux interconnectés et les algorithmes utilisés intègrent les récentes connaissances (ASHLEY et CRABTREE, 1992 ;VERBANCK ef al., 1994) en matière de production, de transport et de caractéristiques de la pollution particulaire (voir figure 1). Les différents algorithmes de génération et de transfert de la pollution du modèle ont été choisis en fonction des résultats du programme « Banc d'essai des algorithmes de modélisation de la pollution par temps de pluie » (ZUG ef al., 1998b).…”
Section: Description Sommaire Du Modèle Horusunclassified